Two new species of Cyta (Acari: Prostigmata: Bdellidae) from Western Iran - Eghbalian, Amir Hossein; Khanjani, Mohammad; Safaralizadeh, Mohammad Hassan; Ueckermann, Edward A. (Zootaxa, 2014)
This paper reports two new species of Bdellidae, Cyta leliae sp. nov. and Cyta kurdistanicus sp. nov., collected from soil and litter under oak trees, Quercus brantii Lindl. (Fagaceae), wild almond, Amygdalus lycioides Spach (Rosaceae) and grass, Kurdistan Province, Iran. A key is provided to adult female Cyta of the world.